2003
DOI: 10.1016/s0735-1097(03)00763-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of immediate stenting after thrombolysis in acute myocardial infarction

Abstract: Immediate stenting after thrombolysis leads to a significant reduction of cardiac events compared with a more conservative approach including delayed stenting after two weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(72 citation statements)
references
References 21 publications
4
63
0
5
Order By: Relevance
“…The outcomes were in keeping with studies in which thrombolysis was followed by frequent revascularization [2, 23,37,38,39,40,41] and suggest that the advantage of PPCI may be attenuated in this setting. The findings are especially relevant for the large number of centers where immediate angiography-intervention facilities are not always available or readily applicable [28].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The outcomes were in keeping with studies in which thrombolysis was followed by frequent revascularization [2, 23,37,38,39,40,41] and suggest that the advantage of PPCI may be attenuated in this setting. The findings are especially relevant for the large number of centers where immediate angiography-intervention facilities are not always available or readily applicable [28].…”
Section: Discussionsupporting
confidence: 80%
“…A meta-analysis revealed a reduction in severe heart failure and improved survival in patients with moderate or large STEMI [33], as did the randomized UK REACT trial [34]. Although studies in the pre-stent and pre-drug eluting stent era and prior to the availability of effective anti-platelet therapy did not support routine revascularization following thrombolysis [35, 36], recent randomized trials did support an invasive approach [37,38,39]. …”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest trials looking at the association was SIAM III done on 197 patients with AMI where one group received angioplasty within six hours of thrombolysis with reteplase and the other after two weeks. It was found that the immediate stenting group had a significant decrease in primary endpoint of ischemic event, death, reinfarction and need for revascularization by 25% [20]. GRACIA 1 is another randomized intent to treat trial, which compared combined endpoints of death, reinfarction and revascularization at 12 months.…”
Section: Role Of Pci In Post Thrombolysis Stable Patientsmentioning
confidence: 99%
“…Diese Empfehlung wurde auf der Stufe I A gegeben und basierte vor allem auf den SIAM-III- [7], GRACIA-1- [8] und CAPITAL-AMI-Studien [9] im Zusammenhang mit den LPLS- [10] und ALKK-Studien [11] sowie AS-SENT-2 [12] und der Metaanalyse der TIMI-4-, -9-und -10b-sowie der IN-TIME-II-Studien [13]. …”
Section: Kommentarunclassified